Dakwah clan Dialektika Budaya Jawa dalam lintasan Sejarah - Sulkhan Chakim (Fakultas Dakwah UIN Prof. K.H. Saifuddin Zuhri, 2008)
The long and continuous interaction process between Islamic preaching (do'wo) and Javanese culture hos resulted in new products of synthetic culture. The emergence of some rituals which shows the combination between loco/ culture forms and Islamic message is acceptable as for as this acculturation maintains the fundomeritol spirit of Islamic teaching. Such prodices ore commonly found nowadays which shows the combination between these two elements, local culture and Islamic values.Â